Estimated sweat loss, fluid and carbohydrate intake, and sodium balance of male major junior, AHL, and NHL players during on-ice practices - Gamble, A. S. D.; Bigg, J. L.; Vermeulen, T. F.; Boville, S. M.; Eskedjian, G. S.; Jannas-Vela, S.; Witfield, J.; Palmer, M. S.; Spriet, L. L. (International Journal of Sport Nutrition and Exercise Metabolism, 2019)
Several previous studies have reported performance decrements in team sport athletes who dehydrated approximately 1.5-2% of their body mass (BM) through sweating. This study measured on-ice sweat loss, fluid intake, sodium balance, and carbohydrate (CHO) intake of 77 major junior (JR; 19 ± 1 years), 60 American Hockey League (AHL; 24 ± 4 years), and 77 National Hockey League (NHL; 27 ± 5 years) players. Sweat loss was calculated from pre- to post-exercise BM plus fluid intake minus urine loss. AHL (2.03 ± 0.62 L/hr) and NHL (2.02 ± 0.74 L/hr) players had higher sweat rates (p < .05) than JR players (1.63 ± 0.58 L/hr). AHL (1.23 ± 0.69%; p = .006) and NHL (1.29% ± 0.63%; p < .001) players had ~30% greater BM losses than JR players (0.89% ± 0.57%). There was no difference in fluid intake between groups (p > .05). Sodium deficits (sodium loss - intake) were greater (p < .05) in AHL (1.68 ± 0.74 g/hr) and NHL (1.56 ± 0.84 g/hr) players compared with JR players (1.01 ± 0.50 g/hr). CHO intake was similar between groups (14-20 g CHO/hr), with 29%, 32%, and 40% of JR, AHL, and NHL players consuming no CHO, respectively. In summary, sweat rates were high in all players, but the majority of players (74/77, 54/60, and 68/77 of JR, AHL, and NHL, respectively) avoided mild dehydration (>2% BM) during 60 min of practice. However, ~15%, 41%, and 48% of the JR, AHL, and NHL players, respectively, may have reached mild dehydration and increased risk of performance decrements in a 90-min practice.